Evaluation of Interleukin 6 and high sensitive C-reactive protein in relation with Body Mass Index - Zaid Nabeel Elia; Nisreen Waleed Mustafa (Diyala Journal of Medicine, 2018)
Background:Obesity is one of the largest public health problem worldwide. It is a multi-factorial chronic disease that increases mortality and the prevalence of heart-related diseases. Adipose tissue secretes large numbers of peptides that resemble cytokines. Interleukin 6 )IL-6( is one of those peptides that are released by adipose tissue. One of the major function of IL-6 is sending signal to liver to secrete C-reactive protein (CRP).